Proposta metodológica de medição da resiliencia agroecológica em sistemas sócio-ecológicos: um estudo de caso nos Andes colombianos - Salazar, Alejandro Henao (2012)
In the last tree centuries the capitalistic economic model introduced deep changes and with no precedents into the ecosystems with the aim to satisfy its own food demands, potable water, wood, fiber and energy. Those changes helped to improve the life of thousands of people, but at the same time weakened nature s regulation capacity. The most evident consequence is the actual threat of a world climate change, which causes a special worry between agriculture scientists once the agriculture could be seriously injured when climate and rainfall regime change, putting in danger food sovereignty in local and global levels. Maybe the most important found in the latest years were the revealing of many agricultures whom can deal with the climate variation and also prepare themselves to minimize the lost of income by using alternative cultural treatment. This study proposes a methodology to measure agroecological resilience in socio ecologic systems, comparing forms of agroecological cultural systems (a) within the conventional cultural systems(c). A technical team gathered with peasantries measured agroecological resilience indicators in agroecological and conventional properties in the central ridge of Colombian Andes. The selected indicators discuss: a) the characterizing of a climate event (threat), b) the estimative of vulnerability level, c) the sustainable agriculture technique capacity to response. This study identified resilience differences between agroecological and conventional properties, showing that agroecological treatments tend to show a bigger resilience capacity in face to climates risks. The definition and the identification of those capacities show the vii potential risk management from the approach to the response and adaptation capacity. And It is especially those peasantries with alternative cultural treatments that were able to deal, resist and recover from extreme meteorological events.